الضمانات الجنائية للحرية الشخصية عند القبض من طرف السلطة القضائية : دراسة تحليلية مقاصدية - شريف، عبد الله عبد السلام محمد (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2020)
This study examines the legal safeguards of personal freedom when arrested by the judicial authority, a comparative study. Arresting a person is considered as one of the serious actions that may deprive one's liberty and it is touching one of the important rights of human beings. The significance of the study is to address a critical and sensitive legal issue both academically and practically, and it aims to balance the interest of the public in ensuring their security and the interest of the individual in protecting his personal freedom. The problem of the study focuses on the adequacy of the legal provisions in the Libyan legislations to protect personal freedom from any kind of infringement, and to achieve harmony and reconciliation between the interest of society in protecting its security and stability, and to ensure the freedoms and rights of individuals from any abuse or arbitrariness by the judiciary. The study also discusses crucial questions about the rights of the arrested persons such as: are they in a situation where they are respected and their dignity and humanity are protected, do they have the opportunity to defend themselves, and what is the legal implication if their rights have been violated. The study adopts the inductive comparative approach, through extrapolating and analyzing the relevant texts of Libyan law, and reviewing the position of Islamic law in this aspect as much as possible. The findings of the study reveal that personal freedom, though it is established an affirmed right in Islamic law, but it is subjected not to cause any harm with it. Libyan law has not clarified the legal nature of the arrest procedure, is it an investigation or an inference procedure? The Libyan legislator did not specify what is meant by sufficient evidence, so it is left to the executives to interpret. Article 26 of the Libyan Code of Criminal Procedure contradicts the principle of innocence. There is no provision in Libyan law affirming the right of the accused to have access to a lawyer and the right to silence during his arrest. The Libyan legislator did not state clearly the state's responsibility for unlawful arrest. Islamic law balances the rights of the accused and the preservation of his original rights with the right of society to punishment, and state rights for the accused to be preserved. These findings are followed by some recommendations which the competent authorities can benefit from them.